Peripheral Nerve Ultrasonography in Chronic Inflammatory Demyelinating Polyradiculoneuropathy and Multifocal Motor Neuropathy: Correlations with Clinical and Neurophysiological Data - Aristide Merola; Michela Rosso; Alberto Romagnolo; Erdita Peci; Dario Cocito (Neurology Research International)
Objective. This cross-sectional study analyzes the pattern of ultrasound peripheral nerve alterations in patients with chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) and multifocal motor neuropathy (MMN) at different stages of functional disability. Material and Methods. 22 CIDP and 10 MMN patients and a group of 70 healthy controls were evaluated with an ultrasound scan of the median, ulnar, peroneal, tibial, and sural nerves. Results were correlated with clinical disability scales and nerve conduction studies. Results. Patients with intermediate functional impairment showed relatively larger cross-sectional areas than subjects with either a milder (p<0.05) or more severe impairment (p<0.05), both in CIDP and in MMN. In addition, MMN was associated with greater side-to-side intranerve variability (p<0.05), while higher cross-sectional areas were observed in CIDP (p<0.05) and in nerve segments with predominantly demyelinating features (p<0.05). Higher CSA values were observed in nerves with demyelinating features versus axonal damage (p<0.05 for CIDP; p<0.05 for MMN). Discussion and Conclusions. Greater extent of quantitative and qualitative US alterations was observed in patients at intermediate versus higher functional disability and in nerves with demyelinating versus axonal damage. CIDP and MMN showed differential US aspects, with greater side-to-side intranerve variability in MMN and higher cross-sectional areas in CIDP.